Biofilm forming rhizobacteria affect the physiological and biochemical responses of wheat to drought - Esmaeil Karimi; Nasser Aliasgharzad; Ezatollah Esfandiari; Mohammad Bagher Hassanpouraghdam; Thomas R. Neu; François Buscot; Thomas Reitz; Claudia Breitkreuz; Mika T. Tarkka (AMB Express, 2022)
Key points Numerous biofilm forming PGPR reside in grass rhizospheres from arid grasslands. Drought tolerance of wheat is enhanced by bacterial inoculations. Wheat variety and the level of drought stress modify the plant’s response to the bacteria.